SOSIALISASI PENANAMAN KARAKTER SALING MENGHARGAI MELALUI DUTA ANTI BULLYING UNTUK SISWA DI SEKOLAH DASAR - Bramantha, Heldie; Syarifa, Mufarrahatus (Fakultas Keguruan dan Ilmu Pendidikan Universitas Abdurachman Saleh Situbondo, 2024)
This activity aims to provide a new understanding of social patterns that have been prevalent in the middle of elementary students. Through the elected and trained “duta anti bullying